Resolvin D1 attenuates sepsis induced acute kidney injury targeting mitochondria and NF-κB signaling pathway. Issue 12 (December 2022) - Wang, Liya; Li, Jiameng; Liao, Ruoxi; Li, Yupei; Jiang, Luojia; Zhang, Zhuyun; Geng, Jiwen; Fu, Ping; Su, Baihai; Zhao, Yuliang
Abstract: Background: Acute kidney injury is a highly common and multifactorial renal disease resulting in significant morbidity and mortality, especially sepsis-induced acute kidney injury. There is no effective therapy available to treat or prevent sepsis-induced acute kidney injury. One of the specialized pro-resolving mediators, Resolvin D1 exhibits special anti-inflammatory effects in several inflammatory disease models, but there is little evidence about the effect and mechanism of Resolvin D1 in sepsis-induced acute kidney injury. Methods: We conducted experiments to explore the effect and mechanism of Resolvin D1 in sepsis-induced acute kidney injury. In vitro, human proximal tubular epithelial cells were used to test the apoptosis ratio, cell viability and reactive oxygen species level. In vivo, C57BL/6 mice were injected with lipopolysaccharide to establish a sepsis-induced acute kidney injury model. Renal function and structure, apoptosis ratio of kidney cells, mitochondrial structure and function and related protein and gene levels were assessed. Results: In vitro, the resolvin D1-treated group showed higher cell viability and lower reactive oxygen species levels and apoptosis ratios than the LPS group. In vivo, Resolvin D1 can not only improve renal function and mitochondrial function but also reduce the apoptosis ratio, while mediating mitochondrial dynamics and inhibiting NF-κB pathway. Conclusions: Resolvin D1 has a good renoprotective effect by maintaining mitochondrial dynamics and inhibiting the NF-κB pathway. Abstract : Sepsis-induced acute kidney injury; RvD1; Mitochondrial function; Apoptosis; NF-κB pathway.